2014
DOI: 10.1016/j.drugalcdep.2014.06.008
|View full text |Cite
|
Sign up to set email alerts
|

A “refugee paradox” for substance use disorders?

Abstract: Background Few, if any, studies have systematically examined the link between nativity and substance use disorders (SUD) among refugees using national samples. As such, it remains uncertain if the “immigrant paradox” for substance use can be extended to include refugees in the United States. Methods Employing data from the National Epidemiologic Survey on Alcohol and Related Conditions, we examine the lifetime prevalence of SUDs among refugees (n = 428) in contrast with non-refugee immigrants (n = 4,955) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 20 publications
1
40
0
1
Order By: Relevance
“…Additionally, in examining the associations between immigration status and mental health disorders, we controlled for diagnoses of lifetime alcohol use disorders (abuse/dependence) as well as lifetime drug use disorders (abuse/dependence on heroin, hallucinogens, cocaine/crack, marijuana, stimulants, painkillers, tranquilizers, or sedatives). Prevalence estimates for substance use disorders among native-born Americans and immigrants are not reported in this study, but are available elsewhere (Salas-Wright and Vaughn, 2014). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, in examining the associations between immigration status and mental health disorders, we controlled for diagnoses of lifetime alcohol use disorders (abuse/dependence) as well as lifetime drug use disorders (abuse/dependence on heroin, hallucinogens, cocaine/crack, marijuana, stimulants, painkillers, tranquilizers, or sedatives). Prevalence estimates for substance use disorders among native-born Americans and immigrants are not reported in this study, but are available elsewhere (Salas-Wright and Vaughn, 2014). …”
Section: Methodsmentioning
confidence: 99%
“…Mental illness risk factors experienced in this phase include prolonged civil conflicts and wars (Goodman, 2004), sexual and physical abuse (Crisp, 2000), separation from family (Paardekooper et al, 1999), and prolonged stays in refugee and other transitionary camps (Steel et al, 2006). Individuals who have endured these experiences report mental health and behavioral disorders, including depression, anxiety, psychosis, anger, violence, and posttraumatic stress disorder (Paardekooper et al, 1999; Steel et al, 2002; Fazel et al, 2005; Pumariega et al, 2005; Steel et al, 2006; Liddell et al, 2013; Salas-Wright and Vaughn, 2014). In the resettlement phase, immigrants often have to contend with and acclimatize to a new socio-cultural and economic environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, this body of research suggests that immigrants to the United States, relative to the native born, are less likely to initiate and develop substance use disorders. Evidence for this phenomenon, also referred to as the "healthy immigrant effect," has been observed among a variety of behavioral (e.g., antisocial behavior, intimate partner violence) and health (e.g., chronic disease, obesity) outcomes as well as among emigrants from various global regions and in multiple receiving nations (Kennedy et al, 2014;Salas-Wright and Vaughn, 2014;Vaughn et al, in press, 2014aVaughn et al, in press, , 2014b. Fundamentally, the paradox is that, despite having disproportionately lower income and education levels, immigrants are often healthier than their native-born counterparts.…”
mentioning
confidence: 99%
“…Investigations from adult samples focused on emigrants from Mexico (Borges et al, 2009(Borges et al, , 2012, the former Soviet Union (Guarino et al, 2012), Asia (Moloney et al, 2008;Wong et al, 2007), and Latin America (Alegría et al, 2008;Ojeda et al, 2008) have found trends similar to those identifi ed in younger samples. Studies of adults in the United States have been hampered by their inability to examine the stability of the relationship between substance use and immigration across multiple immigrant generations or among emigrants from various regions of the world (Johnson et al, 2002;Li and Wen, 2013;Salas-Wright and Vaughn, 2014).…”
mentioning
confidence: 99%